Accounting In The Cultural Perspective of Mbaba Belo Selambar - Rafles Ginting; Albert Nicodemus Sinukaban; Felicia Novi Simanjaya; Khristina Khristina (Jurnal Akuntansi dan Perpajakan, 2023)
This study aims to determine how the dowry cost is determined, or what is commonly called uang tukur in the Mbaba Belo Selambar ceremony, and whether the process is by existing accounting concepts. Accounting is always associated with techniques and calculations. However, in practice, accounting is influenced by many social factors, one of which is the local culture. In Karo traditional marriage, there is a uang tukur set by the families of both parties. Hence, an element of cost is interesting to discuss from an accounting perspective. This research uses qualitative methods with an ethnomethodology approach. Data was collected by interviewing four informants about determining uang tukur in Mbaba Belo Selambar. Based on the research that has been done, it is found that the accounting practice in the Uang tukur tradition is through recording the little money received and will be issued when it is distributed.